Parallel futures? Indigenous resurgence and the haunting of the settler. (August 2022) - Palmer, Jane; Walsh, Angelia; Batorowicz, Beata
Abstract: Two kinds of futures have emerged in the shadow of colonialism: the haunted futures of a white settler society that suppresses or denies knowledge of the 'founding wound' of colonial invasion; and Indigenous futures constituted by a refusal of defeat and a 'radical resurgence.' While they appear as parallel and irreconcilable trajectories, we suggest, after Ahlqvist and Rhisiart (2015, 'Emerging pathways for critical futures research: Changing contexts and impacts of social theory', Futures, vol. 71, pp. 91–104), that a haunting continues to link them; projects of Indigenous refusal and resurgence continue to alert non-Indigenous settler societies to a past not done with, and a futures trajectory based on denial and deception that must be unlearned. We describe one such project of Indigenous resurgence in South West Queensland, Australia, and suggest that it is an example of a local resurgence that performs, through its truth-telling, a 'generative haunting' of white settler society. In doing so, it forges a link between Indigenous and non-Indigenous futures, disturbing, and making more contingent, white settler imaginaries of the past and the future. Highlights: Two kinds of futures emerge in colonialism's shadow: haunted settler futures and Indigenous futures of 'radical resurgence'. While they appear as parallel and irreconcilable trajectories, the haunting of one by the other continues to link them. Projects of Indigenous resurgence remind settler societies of a past not done with, and suggest alternative futures. The SW Queensland Indigenous Cultural Trail performs a 'generative haunting' of white settler society. Through such projects of Indigenous resurgence, the settler might begin the unlearning required to re-imagine the future.